Партеногенетичне активування in vitro яйцеклітин свиней - Остаповець, Л.І. (Фактори експериментальної еволюції організмів, 2008)
Изложены результаты исследований вопроса получения партеногенетических
эмбрионов свиней in vitro. Показана возможность партеногенетического развития
созревших in vitro ооцитов свиней после обработки этанолом до 16-клеточной стадии. The results of investigations of reception parthenogenetic pig embryos in vitro are
given in account. The possibility of parthenogenetic development of in vitro matured porcine
oocytes after treatment with ethanol to 16-cell stage embryos has been showed.